Employee engagement and its relationship towards normative commitment in Malaysia oil and gas industry - Ridwan Mokhtar; Sylvia Nabila Azwa Ambad; Sharifah Nurafizah Syed Annuar; Nelson Lajuni (Macrothink Institute, 2021)
The relationship between employee engagement and organisational commitment has been established and documented in past literature. Hitherto, they are still very relevant and remain a pertinent subject to be discussed, especially with the rapid evolution of business and adjustments in the economic setting. However, much of the focus of past studies were surrounding employee engagement divulging organisational commitment. Only a few studies on the impacts of employee engagement on normative commitment have been shown, especially in Malaysia’s oil and gas industry. We do not adequately know how employee engagement is associated with normative commitment. Hence, this study goals to examine the effects of employee engagement on normative commitment. Two hundred fifty offshore employees participated in this study. Subsequently, 234 completed responses were collected, and Partial Least Squared Structural Equation Modelling were used to analyse the data using Smart PLS 3.3.2 version . The findings advise that employee engagement, particularly organisational engagement dimension, has a positive relationship with both normative commitment dimensions among offshore employees in Malaysia. This study provided oil and gas organisation with a n improved insight and understanding of the significance of the organisational engagement aspect in improving employees’ level of normative commitment among offshore employees. Because of the recent pandemic outbreak, future studies should consider the organisational support rendered by the organisation to offshore employees in predicting the new norms for oil and gas companies. Future studies should also utilise the qualitative approach or employ the Partial Least Square Multi Group Analysis (PLS MGA) to examine whether ethnicity, working tenure, and working locations play an essential role in the relationship between employee engagement and normative commitment.